This abled body : rethinking disabilities in biblical studies - Avalos, Hector; Melcher, Sarah J.; Schipper, Jeremy (Semeia studies ;, 2007)
The essays of This Abled Body engage biblical studies in conversation with the wider field of disability studies. They explore the use of the conceptual category "disability" in biblical and Near Eastern texts and examine how conceptions of disability become a means of narrating, interpreting, and organizing human life. Employing diverse approaches to biblical criticism, scholars explore methodological issues and specific texts related to physical and cognitive disabilities. Responses to the essays by established disability activists and academics working in the social sciences and humanities conclude the volume. --From publisher's description